Childhood horse and donkey bites; a single tertiary health center experience in a rural area - Ibrahim Hakan Bucak (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Background: The aim of this study was to examine the characteristics of patients presenting to a pediatric emergency department in a rural province of Turkey due to horse and donkey bites and to analyze whether these features differ from those of more common animal bites in rural areas. Materials and Methods: The records of patients presenting to the pediatric emergency department of a tertiary hospital due to horse and donkey bites over a 3-year period were examined retrospectively. Demographic data, month of presentation, animal species involved (horse or donkey), the body area bitten, treatment applied to the wound site, whether tetanus and rabies vaccinations were administered, and whether or not antibiotics were prescribed on discharge from the emergency department were recorded from these files. Results: The annual incidence of horse and donkey bites was determined as 7.8/100,000. Thirty-six patients, 24 (66.7%) boys and 12 (33.3%) girls, with a mean age of 95.6 ± 33.9 (48–190) months, were included in the study. Twenty-six patients (72.2%) were bitten by donkeys, and 10 (27.8%) by horses. Bites were most common in September (30.6%). The most commonly bitten areas were the back and/or upper extremities. Rabies vaccination was administered in all cases. Amoxicillin–clavulanic acid was prescribed in 28 (77.8%) cases. Conclusion: Horse and donkey bites are frequently observed in rural areas. The inhabitants of such areas should therefore be educated concerning horse and donkey bites. Health workers encountering such bites should behave in the same way as in more common animal bites in terms of patient management. Our results will be instructive for other developing countries similar to Turkey.